2018
DOI: 10.3892/br.2018.1063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance and biological roles of small nucleolar RNAs in hepatocellular carcinoma (Review)

Abstract: Hepatocellular carcinoma (HCC) is among the most common and fatal cancers. It is a multistage and multifactorial carcinoma, in which a number of factors serve roles in its initiation and progression. Small nucleolar RNAs (snoRNAs), considered to serve a role in various cancers, have recently been identified to have significant contributions to HCC tumorigenesis. Recent studies suggest that snoRNAs have a critical role in the pathogenesis of HCC. Moreover, detailed studies have demonstrated that various snoRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In tissue, we observed a general downregulation of snoRNAs in tumor compared to normal. Studies have shown that snoRNAs are indeed downregulated in tumors [50] and in HCC [51]. In cancer serum vs control serum, snoRNAs were generally up-regulated and tRNAs were generally downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue, we observed a general downregulation of snoRNAs in tumor compared to normal. Studies have shown that snoRNAs are indeed downregulated in tumors [50] and in HCC [51]. In cancer serum vs control serum, snoRNAs were generally up-regulated and tRNAs were generally downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some of the snoRNAs and snoRNPs expression are coordinately upregulated in various types of cancers. For example, box H/ACA and DKC1 are upregulated in breast cancer, and box H/ACA, NOP10 and GAR1 are increased in HNSCC, suggesting that hyperactive snoRNP biogenesis is strongly required for the survival of cancer cells [23,[40], [41], [42]]. Given that the snoRNP complexes need R2TP for their assembly, R2TP expression could be coordinately upregulated in cancer cells.…”
Section: Oncogenesis-related Function Of R2tp/paqosomementioning
confidence: 99%
“…Among them, the lncRNA HULC has already been established as a diagnostic biomarker of HCC 36 . SnoRNAs also show clinical significance and play important roles in HCC 40 . Collectively, we selected five genes as potential exRNA biomarkers for further analysis and validation, including known biomarkers HULC and novel biomarker candidates LINC01226 , circ-0073052 , circ-0080695 , and SNORD3B-1 .…”
Section: Resultsmentioning
confidence: 99%